2009
DOI: 10.1038/sj.bjc.6604853
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive factors and specific histological types of breast cancer: prospective study and meta-analysis

Abstract: Little is known about how reproductive factors affect the risk of breast cancers of different histology. In an analysis of prospective data on 1.2 million middle-aged UK women, we used proportional hazards models to estimate the relative risks of six histological types in relation to menarche, childbearing and menopause. During 8.7 million person-years of follow-up, 17 923 ductal, 3332 lobular, 1062 tubular, 944 mixed ductal lobular, 330 mucinous and 117 medullary cancers were diagnosed. The effect of both age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
63
2
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 21 publications
12
63
2
2
Order By: Relevance
“…According to numerous case-control studies, low parity, older age at the time of birth of the first child, and high socioeconomic status (SES) are established risk factors for breast cancer [4][5][6] for women aged 40 to 49 years, although the association between SES and breast cancer appears to be more pronounced for older/postmenopausal women. [7][8][9] Women with high SES who are diagnosed with breast cancer may have a better survival than women with low SES 10,11 and breast cancer survival appears worse among young/premenopausal and nulliparous women.…”
Section: Introductionmentioning
confidence: 99%
“…According to numerous case-control studies, low parity, older age at the time of birth of the first child, and high socioeconomic status (SES) are established risk factors for breast cancer [4][5][6] for women aged 40 to 49 years, although the association between SES and breast cancer appears to be more pronounced for older/postmenopausal women. [7][8][9] Women with high SES who are diagnosed with breast cancer may have a better survival than women with low SES 10,11 and breast cancer survival appears worse among young/premenopausal and nulliparous women.…”
Section: Introductionmentioning
confidence: 99%
“…Few other studies have reported on exogenous hormone use among night-working women, although ever use of HRT was found to be less common among rotating night shift workers in the Nurses' Health Study, particularly among long-duration night workers (15). Given the established effects of the reproductive and hormonal factors on the risk of breast cancer (16)(17)(18), the differences observed in the current study would put ever night workers, and especially long-duration night workers, at an increased risk of the disease. The differences in family structure and related factors may due to the influence of night work on family life or vice versa; it is possible that women who are not married or living with a partner or are without children are more likely to select and remain in jobs involving night work.…”
Section: Wang Et Almentioning
confidence: 99%
“…Furthermore, histological BC subtypes may differ in their associations with established BC risk factors [8,9,10,11]. The few studies exploring the association between body size and aggressive triple-negative BC (TNBC) reported largely inconsistent results [12].…”
Section: Introductionmentioning
confidence: 99%